Att utveckla undervisningen i förskola på vetenskaplig grund och beprövad erfarenhet: Förskollärares professionella lärande i ett aktionsforskningsprojekt - Ulrika Bergmark; Susanne Westman (Dalarna university, 2022)
The Swedish preschool has undergone some radical education policy changes during recent years, all of which have affected teachers' work. The focus of this article is on the changes relating to the demand for research-based education and how the concept of teaching has been introduced in preschool. The aim of this article was to study preschool-teachers' professional learning in relation to research-based education within an action research project which focused a new conversation method with the children. The theoretical framework of the study was based on social learning theory and communities of practice. The empirical data consists of collegial conversations and written documents produced in the action research project. The results show that the preschool-teachers in a mutual agreement persistently examined and negotiated conversation methods so that they could be adapted to their view of teaching, their professional self, and children and children's participation and learning. Through a common repertoire of scientific tools and social learning processes, they reflected each other's teaching in an open, trustful, and appreciative collaboration, and together, they critically reviewed and problematized their earlier experiences and their teaching in relation to research.